Electricity distribution network design - Lakervi, E. (Erkki) 1945-; Holmes, E. J. 1928- (Institution of Engineering and Technology, 2003)
The following topics are dealt with: The supply system; planning distribution networks; reliability; economic principles; equipment; system protection; HV networks and substations; MV networks; distribution substations and LV networks; load data; network voltage performance; computer-based planning; cooperation in network planning and design.